Synthesis and applications of novel graphene-based composites - Cao, Xiehong (2013)
Graphene, a novel two-dimensional (2D) carbon material, has drawn intensive interest because of its distinct structure and excellent properties. Graphene-based composites are also highly promising in various fields such as electronics, sensors, energy storage, solar cells, and etc. Therefore, the mass production of high-quality graphene and the efficient synthesis of graphene-based composites with controlled morphology and properties are desirable to fulfill the requirements in a broad range of fundamental research and practical applications.